Dipeptidyl peptidase- IV inhibitor alogliptin improves stress-induced insulin resistance and prothrombotic state in a murine model. (November 2016) - Yisireyili, Maimaiti; Takeshita, Kyosuke; Hayashi, Motoharu; Wu, Hongxian; Uchida, Yasuhiro; Yamamoto, Koji; Kikuchi, Ryosuke; Hao, Chang-Ning; Nakayama, Takayuki; Cheng, Xian Wu; Matsushita, Tadashi; Nakamura, Shigeo; et al.
Highlights: Two-week daily restraint stress evoked lipolysis-induced low-grade inflammation in lean murine adipose tissue, and exacerbated insulin resistance and prothrombotic state. Stress-induced adipose inflammation activated in dipeptidyl peptidase-4 (DPP-4) in adipose and plasma. Stress-induced adipose inflammation is correlated to free radical production in adipose, ileum and plasma. DPP-4 inhibitor treatment suppressed stress-induced inflammation, and stress-induced prothrombotic state and insulin resistance. Abstract: Background: Stress evokes lipolytic release of free fatty acid (FFA) and low-grade inflammation in visceral adipose tissue, mediated by increased adipokine secretion, and contributes to glucose metabolism disorder and prothrombotic state. We tested the hypothesis that alogliptin, a dipeptidyl peptidase-4 inhibitor, can ameliorate the biological effects of chronic stress in mice. Method and results: C57BL/6J mice were subjected to 2-week intermittent restraint stress and orally treated with vehicle or alogliptin (dose: 15 or 45 mg/kg/day). Plasma levels of lipids, proinflammatory cytokines (monocyte chemoattractant protein-1, tumor necrosis factor-α, and interleukin-6), and 8-hydroxydeoxyguanosine were measured with enzyme-linked immunosorbent assay. Monocyte/macrophage accumulation in inguinal white adipose tissue (WAT) was examined by CD11b-positive cell count and mRNA expression of CD68 and F4/80 was examined by immunohistochemistry and RT-PCR, respectively. The mRNA levels of the above-mentioned proinflammatory cytokines, NADPH oxidase 4, adiponectin, and coagulation factors (plasminogen activation inhibitor-1 and tissue factor) in WAT were also assessed with RT-PCR. Glucose metabolism was assessed by glucose and insulin tolerance tests, plasma levels of DPP-4 activity, glucagon-like peptide-1, expression of DPP-4, insulin receptor substrate-1 and glucose transporter 4 in WAT and skeletal muscle. Alogliptin administration suppressed stress-induced FFA release, oxidative stress, adipose tissue inflammation, DPP-4 activation, and prothrombotic state in a dose-dependent manner, and improved insulin sensitivity in stressed mice. Conclusions: The results indicate that alogliptin improves stress-induced prothrombotic state and insulin resistance; suggesting that alogliptin could have beneficial therapeutic effects against cardiovascular complications in diabetic patients under stress.